2022
DOI: 10.5397/cise.2021.00542
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative clinical outcomes and radiological healing according to deep and superficial layer detachment in first facet involving subscapularis tendon tear

Abstract: Background: Subscapularis tendon insertion at the first facet has separate layers (deep and superficial). The purpose of this study is to evaluate postoperative clinical outcomes and radiological healing according to each layer of detachment in the first facet involving subscapularis tendon tear. Methods: Eighty-three patients who underwent arthroscopic repair due to First facet involving the scapularis tendon tear accompanying small to medium sized posterosuperior cuff tear were classified into three groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Early detection and prompt repair of subscapularis tears before progression to complex, severe tears with fatty infiltration have been highlighted as a critical factor associated with better outcomes 31 . Outcomes of subscapularis repair are related to tear size and severity 32–34 . Despite age negatively correlating with Constant scores and overall shoulder function, clinical improvement postoperatively can still be achieved in older patients 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early detection and prompt repair of subscapularis tears before progression to complex, severe tears with fatty infiltration have been highlighted as a critical factor associated with better outcomes 31 . Outcomes of subscapularis repair are related to tear size and severity 32–34 . Despite age negatively correlating with Constant scores and overall shoulder function, clinical improvement postoperatively can still be achieved in older patients 35 …”
Section: Discussionmentioning
confidence: 99%
“…31 Outcomes of subscapularis repair are related to tear size and severity. [32][33][34] Despite age negatively correlating with Constant scores and overall shoulder function, clinical improvement postoperatively can still be achieved in older patients. 35…”
Section: Discussionmentioning
confidence: 99%
“…With improvements in shoulder arthroscopy, information about SSC has accumulated. 22,33,41 However, the consensus on large SSC tears and retears remains inconclusive 25,42 ; furthermore, long-term outcome studies of arthroscopic repair for large SSC tears are limited. 35 Previous studies have regarded large SSC tears as follows: (1) complete or full-thickness tears without a clear definition or (2) Lafosse type III and IV tears (upper two-thirds or whole SSC tears).…”
Section: Discussionmentioning
confidence: 99%
“…With improvements in shoulder arthroscopy, information about SSC has accumulated. 22,33,41 However, the consensus on large SSC tears and retears remains inconclusive 25,42 ; furthermore, long-term outcome studies of arthroscopic repair for large SSC tears are limited. 35…”
Section: Discussionmentioning
confidence: 99%
“…Based on this background, Kim et al [ 8 ] evaluated postoperative clinical outcomes and radiological healing of SSC tendon tears according to each layer of detachment in the first facet. This study showed that complete detachment of the deep layer may be related to high retear and low healing rates regardless of detachment of the superficial layer, but also that clinical outcomes may not be related to detachment of specific layers in the first facet.…”
mentioning
confidence: 99%